The Role of Madura Coastal Women in The Public Sphere: Penelitian - Mi’raj Al Abshori; Praptining Sukowati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to examine in depth the reality of public participation among coastal women who are fishermen’s wives in Branta Village, Tlanakan District, Pamekasan Regency, a group that has often been perceived as traditional and constrained by patriarchal culture. Employing a qualitative approach with a sociological perspective, this research explores the lived experiences, subjective meanings, and social practices of coastal women through their involvement in village organizations and community activities, such as the Family Welfare Movement (PKK), integrated health services (posyandu), religious study groups (pengajian), rotating savings groups (arisan), village clean-up activities, coastal environmental conservation, as well as socio-economic activities and non-formal education. The findings indicate that coastal women who are fishermen’s wives in Branta Village, Tlanakan District, Pamekasan Regency, play significant and multidimensional public roles in the fields of education, culture, social life, non-formal politics, and household economy. Women’s involvement as village volunteers and community mobilizers is not merely an extension of their domestic roles but constitutes social practices imbued with values of care, solidarity, collective responsibility, and cultural negotiation. These findings affirm that Madurese culture does not entirely hinder women’s public participation; instead, it provides adaptive spaces that enable women to perform public roles in legitimate and contextually accepted ways. The novelty of this study lies in its interpretation of Madurese coastal women’s participation through everyday social practices and non-formal political engagement, which have received limited attention in mainstream scholarly discourse. Theoretically, this research broadens the understanding of women’s participation by moving beyond the domestic–public and traditional–modern dichotomies. Practically, the findings highlight the importance of gender-sensitive and culturally contextualized village development policies that recognize coastal women as key actors in social sustainability and coastal community development.